Back to the sandbox art and radical pedagogy - Anděl, Jaroslav 1949- (Western Gallery, Western Washington University, 2019)
An international group of artists and scholars reflects on the nature and significance of education in contemporary society, introducing new perspectives on learning and creativity 'Back to the Sandbox' addresses critical issues of the education system from an intriguing new perspective: essays by leading thinkers juxtaposed with art projects, intended for kindergarten through adult. The core issues include democracy in education, creativity, transdisciplinarity, neuroplasticity, thinking versus memorizing, science versus art and humanities. Both artists and scholars explore specific topics while guided by one framing question central to educators' and students' concerns today: What education do we need? The volume includes several lead essays and eighteen shorter texts from international scholars. Based on an exhibition with the same name, Back to the Sandbox records an ongoing multifaceted project that comprises exhibitions, conferences, workshops, surveys, and online roundtables, connecting local communities with international networks. This groundbreaking publication will serve as both reference and inspiration to educators, students, artists, parents, policy makers, and everyone interested in education and art
Keywords: Geschichte; Erziehung -- Motiv; Kunst; Ausstellungskatalog -- Western Gallery -- 09.01.-16.03.2019